The sociopsychological cost of AAE-to-SAE code-switching. (29th May 2022) - Kroll, Tobias A; Townsend, Christopher
Abstract : Objective: This conceptual article outlines the sociopsychological cost that speakers of African American English (AAE) may incur when having to use the Standard dialect of American English (SAE) in academic and professional settings. Its goal is to detail the challenges to speakers' self-concept resulting from this cost, to outline how clinical work may be affected by it, and to issue a call of action to qualitative researchers in the field of communication sciences and disorders. It will be argued that a symbolic interactionist account of identity, informed by qualitative research data, can guide clinicians into action regarding therapy and advocacy. Methods: A contrastive definition of code-switching versus code-mixing/code-meshing or translanguaging will be provided. Existing research, cultural artifacts, and personal accounts will be used to illustrate the sociopsychological cost of code-switching, and the ways in which it can have important impacts on individuals' self-concept and their attitude toward learning. In order to conceptualize these dynamics in interactional terms, Mead's model of the self will be deployed. Results: It can be expected that a sizable portion of African American children and adolescents incur sociopsychological cost when faced with the expectation to code-switch from AAE to SAE at school. This cost can be explained using a Meadian model of identity. Little research has explored this cost, the interactional dynamics in which it is incurred, or its impact on speech-language therapy. Summary and conclusion: Speech-language pathologists' scope of practice includes therapeutic work with students who speak AAE, as well as advocacy for all students, disordered or not, who are faced with the cost of this particular type of code-switching. Qualitative research in the field of communication sciences and disorders is uniquely well suited to illuminate the precise form of the interactional dynamics in question, and to develop ways of addressing them in clinical and advocacy work. Such research should employ a symbolic interactionist model of identity that is not tied to psychological assumptions, but which can be derived entirely from empirical observations.